Certification of specifications for PIM-product powder compositions (after mechanical activation); 4th International Conference on Competitive Materials and Technology Processes - Vasiljeva (Vasilyeva) I. E. Inessa Edvinovna; Vaulina O. Yu. Olga Yurievna; Darenskaya E. A. Elena Anatolievna; Myachin Yu. V. Yury Vladimirovich; Kulkov S. N. Sergey Nikolaevich (2016, 2016)
Title screen